Arthur Upham Pope and a new survey of Persian art - Kadoi, Yuka. (Studies in Persian Cultural History, 2016)
In Arthur Upham Pope and A New Survey of Persian Art , fourteen scholars explore the legacy of Arthur Upham Pope (1881-1969) by tracing the formation of Persian art scholarship and connoisseurship during the twentieth century. Widely considered as a self-made scholar, curator, and entrepreneur, Pope was credited for establishing the basis of what we now categorize broadly as Persian art. His unrivalled professional achievement, together with his personal charisma, influenced the way in which many scholars and collectors worldwide came to understand the art, architecture and material culture of the Persian world. This ultimately resulted in the establishment of the aesthetic criteria for assessing the importance of cultural remains from modern-day Iran. With contributions by Lindsay Allen, Sheila S. Blair, Jonathan M. Bloom, Talinn Grigor, Robert Hillenbrand, Yuka Kadoi, Sumru Belger Krody, Judith A. Lerner, Kimberly Masteller, Cornelia Montgomery, Bernard O'Kane, Keelan Overton, Laura Weinstein, and Donald Whitcomb.